O uso de jogos e a mediação do professor na abordagem histórico-cultural : primeiras aproximações - Pereira, Patrícia (Universidade Federal de São Carlos, 2016)
The present study had as reference the Teaching Activity and Being Learning Situation aimed at internalizing of theoretical knowledge through the action and reflection (both the kids and the researcher) in the search for the solution of problem situations, with the intention to give children the need of appropriation of concepts, worrying about the "Genesis of the concept" (MOURA et al., 2010). The investigative procedure type taken as reference using a Teaching Guiding Activity (TGA) through Being Learning Situations (BLS). It sought to check if the game when used under the historical-cultural approach, triggers learning some own concepts to addition and subtraction operations. It to do so was considered the games CUBRA A SOMA and FECHE A CAIXA. The study consisted of five Teaching Activities with each game, totaling ten activities, during the months of October to December, in the year 2015, in a State school located in the city of São Carlos, in the State of São Paulo. The eight children were selected by the teacher of the class, four considered with more skills in calculus and four considered with less skills in calculus. The procedures included: a) request for authorization of School Unit for realization of this study; b) submission of the study to the Ethics Committee; c) filling a questionnaire for parents/guardians of the eight participating students of this study and the informed consent; d) use of the game CUBRA A SOMA, as activities for the appropriation of addition; e) using the FECHE A CAIXA how activities for the appropriation of addition and subtraction; f) resolution of problem situations involving addition and subtraction; g) footage of children in 10 classes in which were developed the teaching activities and some audio recordings; g) analysis and discuss of data obtained with the footage and audio recordings with the assumption the concepts of cultural-historical approach, the question of study and objectives. The results indicated that the mediations, associated with the motivation of children, during the Teaching Activity can provide the development. Whereas that the children do not generalize and do not internalize the concepts same way, though to be mediated by the same person (the researcher), we found that the knowledge related to the concepts of addition and subtraction were appropriate at different levels.
The use of games and the mediation of the teacher in historical-cultural approach : first approximations
Keywords: Atividade de ensino; Atividade de aprendizagem; Mediação; Motivação; Jogos; Adição; Subtração; Teaching activity; Learning activity; Mediation; Motivation; Games; Addition; Subtraction; CIENCIAS HUMANAS::EDUCACAO